2020
DOI: 10.11604/pamj.2020.37.264.24526
|View full text |Cite
|
Sign up to set email alerts
|

Individual awareness and treatment effectiveness of hypertension among older adults in Ghana: evidence from the World Health Organization study of global ageing and adult health wave 2

Abstract: Introduction the aim of this study was to report the prevalence of hypertension, its awareness and treatment effectiveness among older adults (aged 50 years and above) in Ghana. Methods the Ghana World Health Organization´s (WHO) Study on Global Aging and Adult Health (SAGE) wave 2 dataset was used in this study. The study adopted a cross-sectional study design. Information on self-reported hypertension as well as measured hypertension was analyzed. The level of awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
0
0
Order By: Relevance
“…Our study revealed that approximately one in every two older adults surveyed are hypertensive, reporting an age-standardized prevalence of 46.00% (CI: 41.20 -49.30). This finding is consistent with findings of a recent cross-sectional study by Calys-Tagoe and colleagues who, using data from Global Study on Aging and Adult Health (SAGE) wave 2, reported a prevalence of 50.7% (CI: 48.30 -53.20) among adults aged 50 years and above in Ghana (20). The relatively lower prevalence reported in this study compared to the latter study could be due to the lower ages of 40 -49 years included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that approximately one in every two older adults surveyed are hypertensive, reporting an age-standardized prevalence of 46.00% (CI: 41.20 -49.30). This finding is consistent with findings of a recent cross-sectional study by Calys-Tagoe and colleagues who, using data from Global Study on Aging and Adult Health (SAGE) wave 2, reported a prevalence of 50.7% (CI: 48.30 -53.20) among adults aged 50 years and above in Ghana (20). The relatively lower prevalence reported in this study compared to the latter study could be due to the lower ages of 40 -49 years included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…This data indicates that the country has a poor diagnosis rate for HTN and a low treatment‐seeking behavior. Furthermore, our study's rate of undiagnosed and untreated HTN was comparable to other earlier studies carried out in areas with limited resources, including Ghana (65%, 22.2%), 31 India (42.3%, 6%), 32 Pakistan (58.1%, 25.2%), 33 and Nepal (57.3%, 24.1%) 34 . These results demonstrate that more treatment and screening coverage is needed even though considerable progress has been made.…”
Section: Discussionsupporting
confidence: 88%